2022
DOI: 10.1007/s10695-022-01046-8
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-enriched Bacillus subtilis reduces the effects of mercury-induced on inflammation and intestinal microbes in carp (Cyprinus carpio var. specularis)

Abstract: in common carp. The common carp was exposed to Hg (0.03 mg/L), and 10 5 cfu/g Se-rich B. subtilis was added to the feed. After 30 days of feeding, samples were taken to evaluate the growth performance, serological response, inflammatory response, and intestinal microbial changes. In this study, when fish were exposed to Hg, the growth performance of the Se-rich B. subtilis plus 0.03 mg/L Hg fish group was lower than that of the control group and higher than 0.03 mg/L Hg; The levels of serum immunoglobulin M (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…We have been unable to find studies pertaining the combined effect of L. plantarum and Se 0 Nps on lysozyme activity in vertebrates. However, Shang et al [ 135 ] reported a significantly higher activity of blood lysozyme in carps ( Cyprinus carpio var. specularis ) exposed to Hg for 30 days when their food was supplemented for 30 days with Se-enriched, not in the form of nanoparticles, probiotic Bacillus subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…We have been unable to find studies pertaining the combined effect of L. plantarum and Se 0 Nps on lysozyme activity in vertebrates. However, Shang et al [ 135 ] reported a significantly higher activity of blood lysozyme in carps ( Cyprinus carpio var. specularis ) exposed to Hg for 30 days when their food was supplemented for 30 days with Se-enriched, not in the form of nanoparticles, probiotic Bacillus subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…[ [19][20][21][22] Se-enriched Bacillus subtilis Carp Against oxidative stress and relieve the inflammatory response; reduce the abundance of pathogenic bacteria. [23,24] Se-enriched Bacillus subtilis yb-1114246 Chicken Alleviate the inflammatory response and improve the whole immune status. [14,25] Se-enriched Pediococcus acidilactici MRS7 Mice Regulate oxidative stress and inflammatory factors; maintain mucosal barriers; promote the expression of TJ protein.…”
Section: Species Model Function Referencementioning
confidence: 99%
“…[56,57] On the one hand, Se-enriched probiotics eliminate the inflammatory response by upregulating IL-10, preventing the decrease of transforming growth factor-𝛽, increasing the expression of inhibitor of NF-𝜅B and decreasing the corresponding NF-𝜅B p65 expression. [24,58,59] On the other hand, Seenriched probiotics greatly improve immunity by enhancing the T lymphocyte-surface receptor activity and transformation ability to mitogen, which may be related to the expression of IL-2, an important influencing factor for T cell proliferation. Se-enriched probiotics were initially recognized as Toll-like receptor 2 (TLR2) in the ileal mucous membrane that was subsequently presented to myeloid differentiation factor 88, which stimulated the NF-𝜅B1 signaling pathway to increase the expression of beta defensin-1 that plays a pivotal role in mucosal immunity, especially protection against intestinal infection.…”
Section: Species Model Function Referencementioning
confidence: 99%
“…Recent findings have indicated that environmental pollutants, such as antibiotics, heavy metals, and industrial wastewater, can affect the composition of the intestinal flora, lead to physiological dysfunction, and even cause certain diseases ( Jin et al, 2017 ; Miao et al, 2022 ). Exposure to mercury increases the levels of Aeromonas hydrophila and Aeromonas sobria in the carp intestine and thus affects the intestinal health and increases the levels of pathogenic bacteria ( Shang et al, 2022 ). Therefore, it is particularly important to maintain a healthy intestinal flora.…”
Section: Introductionmentioning
confidence: 99%